What happens when a whole-school health promotion research trial ends? a case study of the SEHER program in India - Shinde, Sachin; Raniti, Monika; Sharma, Amit; Sawyer, Susan M. (Frontiers in Psychiatry, 2023)
Background: Health promotion interventions that are developed and evaluated by researchers and other external providers are at risk of not being sustained beyond the initial implementation period. When delivered by a lay school health worker, the SEHER study of a whole-school health promotion intervention in Bihar, India was found to be feasible, acceptable and effective in improving school climate and student health behaviors. The objective of this case study is to describe the decision-making processes, barriers, and enablers to continuing the SEHER intervention following its official closure. Methods: For this exploratory qualitative case study, data were collected from four government-run secondary schools, two of which continued SEHER and two of which discontinued it after official closure. Thirteen school staff were interviewed, and 100 girls and boys (aged 15-18 years old) participated in eight focus groups discussing their experiences of the process of continuing the intervention (or discontinuing) following its official closure. Thematic analysis was conducted in NVivo 12 using grounded theory. Results: No school sustained the intervention as originally delivered in the research trial. In two schools, the intervention was adapted by selecting sustainable components, whereas in two others it was discontinued altogether. We identified four interrelated themes that explained the complex decision-making process, barriers, and enablers related to program continuation: 1) understanding of the intervention philosophy among school staff; 2) school capabilities to continue with intervention activities; 3) school attitudes and motivation about implementing the intervention, and; 4) the education policy environment and governance structures. Suggestions for overcoming barriers included adequate resource allocation; training, supervision, and support from external providers and the Ministry of Education; and formal government approval to continue the intervention. Conclusions: Sustaining this whole-school health promotion intervention in low-resource school settings in India depended on individual, school and government factors as well as external support. These findings suggest that health interventions will not necessarily become embedded in a school’s operations merely because they are designed as a whole-school approach or because they are effective. Research should identify the resources and processes required to balance planning for future sustainability while awaiting trial results about an intervention’s effectiveness.